EDUKASI TENTANG PENGETAHUAN, SIKAP DAN PERILAKU MASYARAKAT TERHADAP PENCEGAHAN DEMAM BERDARAH DENGUE (DBD) - Salikunna, Nur Asmar; Rahma Badaruddin; Muh. Zainul Ramadhan; Vera Diana Towidjojo; Adi Widhiastu (JURNAL PENGABDIAN FARMASI DAN SAINS, 2022)
Dengue hemorrhagic fever (DHF) is a disease caused by the dengue virus with Aedes aegypti as the main vector. Diseases (DHF) can cause death and cases tend to fluctuate from year to year in Indonesia, including Palu City. Therefore, we carry out community service for the prevention of DHF in Palu City. As for the activities that we carried out in the form of distributing questionnaires, educating the community around the final waste disposal site in the Kawatuna village. The education we provide is the eradication of mosquito nests through the application of 3M Plus, including draining water reservoirs, closing water reservoirs, recycling used goods that can potentially become mosquito breeding grounds. In addition to education, we also provide mosquito repellent lotion for use during the day.The service that we have done can make the community around the final waste disposal site aware of the importance of preventing dengue fever and can be seen from the enthusiasm of relevant stakeholders and the local community.